Developing a simulator for multispectral optoacoustic tomography - Maneas, Efthymios; Tzoumas, Stratis; Ntziachristos, Vasilis; Spyrou, George (13th IEEE International Conference on BioInformatics and BioEngineering, IEEE BIBE 2013, 2013)
The aim of this study was the development of a simulator for Multispectral Optoacoustic Tomography (MSOT). The modelling pathway of the simulator was separated into the optical, the acoustic and the reconstruction part in generating finally a photoacoustic image. In this paper, the presented simulation geometry was based on a recently developed MSOT imaging system, but it can be easily modified to other imaging geometries. Through comparison between experimental and simulated data, a validation of the model as well as its limitations, perspectives and modifications are presented. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-08